1992
DOI: 10.1002/jmv.1890370309
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HCV RNA in saliva, urine, seminal fluid, and ascites

Abstract: Approximately half of the patients with type C hepatitis do not have a history of parenteral exposure. The route of nonparenteral infection remains unknown. To evaluate the possible role of body fluids, the existence of hepatitis C virus (HCV) RNA in saliva, urine, seminal fluid, and ascites was examined by "nested" polymerase chain reaction (PCR). Amplification of the HCV 5' noncoding sequences was carried out. The amplified product was confirmed by Southern blot hybridization and restriction endonuclease dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
2
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(81 citation statements)
references
References 22 publications
(11 reference statements)
3
66
2
10
Order By: Relevance
“…In studies of HCV detection in saliva, urine, and semen, this was also a crucial problem. [18][19][20][21][22][23] They detected 1/1,000 less HCV RNA in these secretions than in sera, which might have been a result of blood contamination. 18,19 In contrast, our comparison of HCV RNA titers between bile and serum showed that HCV RNA levels in bile were as high as those in serum.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of HCV detection in saliva, urine, and semen, this was also a crucial problem. [18][19][20][21][22][23] They detected 1/1,000 less HCV RNA in these secretions than in sera, which might have been a result of blood contamination. 18,19 In contrast, our comparison of HCV RNA titers between bile and serum showed that HCV RNA levels in bile were as high as those in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Blood in the saliva samples may contribute to these discrepant results. We did not perform specific tests to investigate the possibility of occult blood in the saliva samples, Liou et al [1] and Komiyama et al [5] demonstrated that the presence of blood in saliva samples did not correlate with the presence of HCV-RNA in the same samples.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of 38 publications reported100% HCV-RNA detection in saliva samples from HCV-positive patients [16,17,25,29,38]; however, only a few cases or only patients with sialoadenitis were considered in these studies, which may represent a caveat. When reports with sample sizes larger than 30 HCV-positive patients were considered separately, the broad variability of frequencies was evident, ranging from 0 to 66% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This variation in HCV-RNA detection frequencies in saliva samples may be due to the saliva sampling method used.…”
mentioning
confidence: 99%
“…However, HCV RNA has been measured in the saliva of infected individuals independent of mucosal lesions and periodontal disease (Liou et al 1992, Fabris et al 1999, Hermida et al 2002, Lins et al 2005. Additionally, HCV could enter the saliva via peripheral blood mononuclear cells (PBMCs) (Roy et al 1998, Fabris et al 1999, Maticic et al 2001; however, the presence of HCV RNA in PBMCs and saliva have not been closely correlated (Young et al 1993).…”
mentioning
confidence: 99%